Perbedaan Kenaikan Berat Badan pada Bayi yang Mendapat ASI Eksklusif dengan ASI Parsial di Puskesmas Jetis Kota - Asti Norma; Ircham Machfoedz; Oktaviana Maharani (Alma Ata University Press, 2015)
Current conditions in developing countries was approximately 10 million infants were dying. These may be pressed by exclusive breastfeeding, because breastfeeding has been proven to improve the health status of the baby. Based on the baseline study conducted in Puskesmas Jetis Kota, the results of four infants exclusively breastfed resulted in weight gain between 4.800 to 6.100 grams while six partially breastfed infants weight gain between 3.350 to 5.250 grams. The purpose of this study was to determine differences of weight gain in infants between exclusive and partial breastfeeding at Puskesmas Jetis Kota. The study was an inductive study with cross-sectional design. The sampling technique was done by total sampling resulting on 20 couples of mothers and babies who had been exclusively breastfed or received partialy breastfed.This study was conducted at Puskesmas Jetis Yogyakarta on February until March, 2015 and analyzed using “t” test analysis. The results showed that weight gain of exclusively breastfed infants was 8.200 grams and the average of increase in weight gain in infants who are breastfed partial was 7.990 grams. There was 210 gram weight gain more higher in infants with exclusively breastfed. In conclusion, there was no signiﬁcant differences weight gain in infants with exclusively breastfed and partially breastfed infants.